Effects of footwear and foot strike patterns on patellofemoral joint and Achilles tendon loading in novice runners and experienced runners - Li, Yuxin; Nie, Yuhang; Zhang, Xini; Gu, Yaodong (Frontiers in Sports and Active Living, 2025)
IntroductionThis study aimed to investigate the differences in the loading characteristics of the patellofemoral joint (PFJ) and the Achilles tendon (AT) between novice and experienced runners across different footwear conditions (conventional vs. minimalist shoes) with rearfoot striking (RFS) and forefoot striking (FFS).MethodsEleven male RFS novice runners and experienced runners were randomly asked to run across a force platform at 12 km/h when wearing conventional and minimalist shoes with RFS and FFS, respectively. AT and PFJ loading were estimated from kinematic and kinetic data. The morphological (length and cross-sectional area) of AT in vivo were recorded using ultrasound imaging. Three-way ANOVA was used to determine differences in PFJ and AT loading characteristics.ResultsPatellofemoral contact force and AT impulses were significantly greater (p < 0.05) in novice runners than in experienced runners, regardless of footwear or the foot strike pattern. Regardless of running level, patellofemoral contact force and PFJ stress were significantly lower in FFS than in RFS, whereas AT force, AT impulse, and peak AT stress were significantly greater in FFS than in RFS. Peak impact loading rates were significantly lower in conventional shoes with RFS than in minimalist shoes (p < 0.05).DiscussionNovice runners experienced a significant increase in PFJ and AT loads during running. In addition, FFS increased the impulse, force, and stress on the AT and decreased the PFJ stress. Therefore, novice runners need to gradually adjust their foot strike pattern according to the loading capacity of different joints to reduce the corresponding injury risk.